2021
DOI: 10.1002/mabi.202100326
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Incorporation of Quaternary Ammonium Silane Antimicrobial into Self‐Crosslinked Type I Collagen Scaffold: A Hybrid Formulation for 3D Printing

Abstract: Novel 3D‐biomaterial scaffold is constructed having a combination of a new quaternary ammonium silane (k21) antimicrobial impregnated in 3D collagen printed scaffolds cross linked with Riboflavin in presence of d‐alpha‐tocopheryl poly(ethyleneglycol)‐1000‐succinate. Groups of “0.1% and 0.2% k21”, and “0.1% and 0.2% Chlorhexidine (CHX)” are prepared. k21/CHX with neutralized collagen is printed with BioX. Riboflavin is photo‐activated and examined using epifluorescence for Aggregatibacter actinomycetemcomitans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Recently, R-UV-CXL has gradually entered the research field of medical devices and BTE. For example, Bapat et al reported that 3D-printed collagen scaffolds impregnated with quaternary ammonium silane and crosslinked with riboflavin and UV produced a promising scaffold with antimicrobial potency and structural stability [ 90 ]. R-UV-CXL has also been studied in the fields of wound healing [ 91 ], skin repair [ 92 ], cardiac valves [ 93 ], and vascular regeneration [ 94 ].…”
Section: Exogenous Collagen Modificationsmentioning
confidence: 99%
“…Recently, R-UV-CXL has gradually entered the research field of medical devices and BTE. For example, Bapat et al reported that 3D-printed collagen scaffolds impregnated with quaternary ammonium silane and crosslinked with riboflavin and UV produced a promising scaffold with antimicrobial potency and structural stability [ 90 ]. R-UV-CXL has also been studied in the fields of wound healing [ 91 ], skin repair [ 92 ], cardiac valves [ 93 ], and vascular regeneration [ 94 ].…”
Section: Exogenous Collagen Modificationsmentioning
confidence: 99%
“…included the antimicrobial substance quaternary ammonium silane (k21) in the COL scaffold and demonstrated that the scaffold's porosity (45% ± 5.5%) was not substantially different from the original scaffold's porosity while the scaffolds’ elastic modulus increased. [ 91 ] Finally, Perez‐Puyana et al. also improved the elastic modulus of the scaffolds by modulating the COL concentration or adding GA to the initial solution.…”
Section: Different Materials Scaffoldsmentioning
confidence: 99%
“…From the clinical viewpoint, it is anticipated that, in the near future, customized 3D scaffolds can be fabricated as per the anatomy of the osseous defects that will ensure complete coverage of the defects with these antimicrobial scaffolds enhancing bone regeneration. Manufacturing of customized 3D collagen scaffolds as per the architecture of osseous defects is considered an innovation in clinical dentistry for increasing the longevity of teeth (Bapat et al, 2021). In vitro research should be performed to investigate SrtA inhibitory activity of QAS.…”
Section: Future Prospectsmentioning
confidence: 99%